The Sacred in Twentieth-Century Politics
X, 291 p.
Keywords: The emerging shape of the post Cold War world provides evidence that rather than diminishing, the profound intersection of political ideology and religious forms of belief is an ever more potent force in world affairs. This volume offers both theoretic underpinnings, and a comparative analysis that elucidates this potent and dangerous phenomenon.